Sex Differences in Cerebral Small Vessel Disease: A Systematic Review and Meta-Analysis - Jiménez-Sánchez, Lorena; Hamilton, Olivia K. L.; Clancy, Una; Backhouse, Ellen V.; Stewart, Catriona R.; Stringer, Michael S.; Doubal, Fergus N.; Wardlaw, Joanna M. (Frontiers in Neurology, 2021)
Background: Cerebral small vessel disease (SVD) is a common cause of stroke, mild cognitive impairment, dementia and physical impairments. Differences in SVD incidence or severity between males and females are unknown. We assessed sex differences in SVD by assessing the male-to-female ratio (M:F) of recruited participants and incidence of SVD, risk factor presence, distribution and severity of SVD features. Methods: We assessed four recent systematic reviews on SVD and performed a supplementary search of MEDLINE to identify studies reporting M:F ratio in covert, stroke or cognitive SVD presentations (registered protocol: CRD42020193995). We meta-analyzed differences in sex ratios across time, countries, SVD severity and presentations, age and risk factors for SVD. Results: Amongst 123 relevant studies (n = 36,910 participants) including 53 community-based, 67 hospital-based and 3 mixed studies published between 1989 and 2020, more males were recruited in hospital-based than in community-based studies (M:F = 1.16 (0.70) vs M:F = 0.79 (0.35), respectively; p < 0.001). More males had moderate to severe SVD (M:F = 1.08 (0.81) vs M:F = 0.82 (0.47) in healthy to mild SVD; p < 0.001), and stroke presentations where M:F was 1.67 (0.53). M:F did not differ for recent (2015-2020) versus pre-2015 publications, by geographical region, or age. There were insufficient sex-stratified data to explore M:F and risk factors for SVD. Conclusions: Our results highlight differences in male-to-female ratios in SVD severity and amongst those presenting with stroke that have important clinical and translational implications. Future SVD research should report participant demographics, risk factors and outcomes separately for males and females.